What Does Context Have to Do With Anything? A Study of Professional Identity Formation in Physician-Trainees Considered Underrepresented in Medicine. (October 2020) - Wyatt, Tasha R.; Rockich-Winston, Nicole; Taylor, Taryn R.; White, DeJuan
Abstract : Purpose: Research on professional identity formation has largely ignored how race, ethnicity, and the larger sociohistorical context work to shape medical students' professional identity. Researchers investigated how physician-trainees considered underrepresented in medicine (URM) negotiate their professional identity within the larger sociohistorical context that casts them in a negative light. Method: In this qualitative study, 14 black/African American medical students were recruited from the Medical College of Georgia at Augusta University and Emory University College of Medicine between September 2018 and April 2019. Using constructive grounded theory and Swann's model of identity negotiation, the authors analyzed interview data for how students negotiate their racial and professional identities within medical education. Results: The results indicated that URM students were aware of the negative stereotypes ascribed to black individuals and the potential for the medical community to view them negatively. In response, students employed identity cues and strategies to bring the community's perceptions in line with how they perceived themselves—black and a physician. Specifically, students actively worked to integrate their racial and professional identities by "giving back" to the African American community. Community-initiated mentoring from non-URM physicians helped to reify students' hope that they could have a racialized professional identity. Conclusions: Race, ethnicity, and the larger sociohistorical context is often overlooked in professional identity formation research, and this omission has resulted in an underappreciation of the challenges URM physicians' experience as they develop a professional identity. Within the context of this study, findings demonstrated that black/African American physicians negotiated the formation of professional identity within a challenging sociohistorical context, which should be given greater consideration in related research. Abstract : Supplemental Digital Content is available in the text.